Protective effects of exercise on heart and aorta in high-fat diet-induced obese rats. (April 2019) - Acikel Elmas, Merve; Cakıcı, Seyit Enes; Dur, Ismail Rahmi; Kozluca, Ibrahim; Arınc, Melih; Binbuga, Berkant; Bingol Ozakpınar, Ozlem; Kolgazi, Meltem; Sener, Goksel; Ercan, Feriha
Highlights: Moderate swimming exercise (EXC) ameliorated high fat diet induced cardiac and aortic tissue damages. Moderate EXC modulates oxidative stress and NO activity, in both cardiac and aortic tissues. EXC may protect obesity-induced cardiac and aortic damage by regulating the balance of oxidants/antioxidants and NO metabolism. Abstract: We investigated the protective effects of swimming exercise on high-fat diet-induced heart and aorta damage by evaluating oxidative stress and the endothelial nitric oxide (NO) system. Sprague Dawley rats were fed either standard chow (STD, 6% fat) or high-fat diet (HFD; 45% fat) for 18 weeks, with half of the animals trained by daily swimming sessions (EXC; 1 h per day for 5 days/week) for the last 6 weeks of the experimental period and half kept sedentary (SED). Heart and aorta tissues were prepared for routine light and electron microscopy evaluation. Endothelial NOS (eNOS) and inducible NOS (iNOS) distribution in the tissue samples were examined by immunohistochemistry. Biochemical examinations, including blood serum lipid profiles, malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), and tissue NO levels were measured. Deteriorated heart and aorta morphology, increased MDA levels and iNOS-immunoreactivity (iNOS-ir), as well as decreased GSH, NO, SOD, and eNOS-ir parameters were observed in the HFD + SED group. These morphological and biochemical parameters were ameliorated in the HFD + EXC group. Our study revealed that obesity-induced iNOS activation and increased oxidative stress in cardiac and aorta tissues. Exercise protected the obesity-induced cardiac and aortic tissue damage by modulating oxidant/antioxidant balance via involvement of the NO system.